POSTPARTUM PERFORMANCE AS INFLUENCED BY BODY WEIGHT CHANGES AT PARTURITION IN BUFFALOES - MAVI, P S; BAHGA, C S; VERMA, H K; UPPAL, S K; SIDHU, S S (The Indian Journal of Animal Reproduction, 2011)
Twenty normal parturient Murrah buffaloes were divided into 2 groups of 10 each depending upon their bodyweight loss at parturition compared to the one week prepartum, i.e. Group I (G I) lost more than 10% while GroupII (G II} lost less than 10%, The animals in GI continued to loose more weight than Gll till 8"' week postpartum.Lowest body weight was recorded at 6"' week postpartum in both the groups followed by an increase thereafter.' Milk yield continued to increase till 4"'weekin GI and 5th week postpartum in G II followed by a decline.A negative(r = -0.495, P
Keywords: POSTPARTUM PERFORMANCE; BUFFALOES; body weight